American Parishes Remaking Local Catholicism - Adler, Gary J.; Bruce, Tricia C.; Starks, Brian (Fordham University Press, 2019)
Parishes are the missing middle in studies of American Catholicism. Between individual Catholics and a global institution, the thousands of local parishes are where Catholicism gets remade. American Parishes showcases what social forces shape parishes, what parishes do, how they do it, and what this says about the future of Catholicism in the United States. Expounding an embedded field approach, this book displays the numerous forces currently reshaping American parishes. It draws from sociology of religion, culture, organizations, and race to illuminate basic parish processes, like leadership and education, and ongoing parish struggles like conflict and multiculturalism. American Parishes brings together contemporary data, methods, and questions to establish a sociological re-engagement with Catholic parishes and a Catholic re-engagement with sociological analysis. Contributions by leading social scientists highlight how community, geography, and authority intersect within parishes. It illuminates and analyzes how growing racial diversity, an aging religious population, and neighborhood change affect the inner workings of parishes. Contributors: Gary J. Adler Jr., Nancy Ammerman, Mary Jo Bane, Tricia C. Bruce, John A. Coleman, S.J., Kathleen Garces-Foley, Mary Gray, Brett Hoover, Courtney Ann Irby, Tia Noelle Pratt, and Brian Starks
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Jul 2020)
Keywords: Catholicism; Congregations; Field Theory; Organizations; Parish Life; Parish Trends; Parishes; SOCIAL SCIENCE / Sociology of Religion; Catholics -- United States